Khuluwwu Al-Rijli Wa Takayyuhu Fi Al-Mu'amalah Al-Mu'ashirah - Tamyiz Muharram (Millah: Journal of Religious Studies, 2005)
This paper tries to study the permanent leasing practice (khuluwwu al-rijl) in contemporary mu'amalah. According to the writer, the reality of our society today needs the fixed or permanent leasing. Therefore, the reorientation of leasing such astounding classical fiqh book is something very important. The writer with any arguments, argue that the permanent leasing is the need of contemporary of muamalah fiqh which must be appreciated. Finally, for the effectiveness of such leasing, the government should intervene with any regulating policies.